2016
DOI: 10.1021/acs.langmuir.6b00845
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Behavior and Segment Concentration Profile of Densely Grafted Polymer Brushes Swollen in Vapor

Abstract: The scaling of the thickness, hs, of a densely grafted polymer brush of chain length N and grafting density σ swollen in vapor agrees quantitatively with the scaling reported by Kuhl et al. for densely grafted brushes swollen in liquid. Deep in the brush, next to the substrate, the shape of the segment concentration profile is the same whether the brush is swollen by liquid or by vapor. Differences in the segment concentration profile are manifested primarily in the swollen brush interface with the surrounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Indeed, Sun et al found results consistent with solvent enrichment at the liquid–air interface for neutron reflectivity (NR) measurements of polystyrene brushes in toluene vapor. 31 Furthermore, their experimental results and self-consistent field theory indicate that the polymer density profiles of these brushes are similar to the expected parabolic profiles for brushes in liquid, mainly deviating in the fact that the polymer density abruptly drops to zero near the free interface rather than decaying gradually. Another NR study on brushes of the weak polyelectrolyte poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) in humid air by Galvin et al showed similarly enhanced water concentrations near the air interface.…”
Section: Fundamentalsmentioning
confidence: 73%
See 1 more Smart Citation
“…Indeed, Sun et al found results consistent with solvent enrichment at the liquid–air interface for neutron reflectivity (NR) measurements of polystyrene brushes in toluene vapor. 31 Furthermore, their experimental results and self-consistent field theory indicate that the polymer density profiles of these brushes are similar to the expected parabolic profiles for brushes in liquid, mainly deviating in the fact that the polymer density abruptly drops to zero near the free interface rather than decaying gradually. Another NR study on brushes of the weak polyelectrolyte poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) in humid air by Galvin et al showed similarly enhanced water concentrations near the air interface.…”
Section: Fundamentalsmentioning
confidence: 73%
“… 25 , 26 Moreover, previously outlined applications such as antifouling 27 and lubrication 28 30 may also be extended to surfaces in air. However, polymer brushes in air deviate qualitatively from their behavior in liquids, both at interfaces 31 and in the bulk. 32 This has given rise to new scientific questions that need answering to enable and optimize the application polymer brushes in air.…”
Section: Introductionmentioning
confidence: 91%
“…The observation of an enhanced solvent density at the top of the brush for highly swollen brushes is consistent with experimental observations. 21 , 23 Yet, it appears to clash with the self-consistent field theory by Cohen Stuart et al, 53 which indicates the possibility of chain segments adsorbing at the brush–air interface for low ϵ pp . We attribute the absence of a polymer-enriched phase at the interface to the relatively high entropic penalty for chain stretching, which arises from the relatively short chain length and high grafting density we employ in our simulations.…”
Section: Results and Discussionmentioning
confidence: 97%
“…However, neutron reflectometry measurements of vapor-solvated brushes indicate that the brush density decreases as a function of the distance from the anchoring surface. 23 Another assumption in the basic Flory–Huggins model is that brush swelling is independent of the grafting density, while experimentally, it is found that the swelling increases with decreasing grafting density. 24 A model that includes the entropic penalty for polymer stretching allows for predicting grafting density effects, even in a mean-field approach.…”
Section: Introductionmentioning
confidence: 99%
“… 25 27 For the vapor-solvated brushes, this can be expected since neutron reflectivity measurements indicate block density profiles with a sharper decay than observed for liquid-solvated brushes. 28 See the Supporting Information for further details on the ellipsometry models and experimental procedures ( Figures S7, S8, and S9 ).…”
Section: Methodsmentioning
confidence: 99%